Large B cell lymphoma of the subtalar and talonavicular joint synovium. (30th January 2013) - George, David Alexander; Afsharpad, Arash; Chifu, Mihai Daniel; Ray, Pinak
Abstract : We present the unique case of a 68-year-old man with a background of rheumatoid arthritis, who underwent left subtalar and talonavicular arthrodesis due to degenerative changes and chronic pain. Histology of the synovium demonstrated large B cell lymphoma. The patient subsequently underwent R-CHOP chemotherapy and radiotherapy to the affected area. This is the first described case of a primary large B cell lymphoma of the subtalar and talonavicular joints, without bony involvement.